DESAIN KONSEPTUAL PLATFORM E-LEARNING UNTUK PEMBELAJARAN AL-QUR’AN DAN HADITS BERBASIS LEARNING MANAGEMENT SYSTEM DENGAN FITUR INTERAKTIF - Lestari Muzdalena; Rasyidi (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
The rapid development of digital technology has encouraged the use of Learning Management Systems (LMS) in higher education, including in the teaching of the Qur’an and Hadith. However, LMS implementation in this context remains largely administrative and content-oriented, with limited pedagogical design to support meaningful learning engagement and value internalization. This study aims to formulate a conceptual design of an LMS-based e-learning platform for Qur’an and Hadith learning with pedagogically relevant interactive features. The study employs a qualitative approach using conceptual design research based on a literature review, synthesizing national and international publications from the last five years on e-learning, LMS, digital pedagogy, and Qur’an and Hadith education. The findings indicate that an effective LMS design for Qur’an and Hadith learning should be grounded in four key principles: pedagogical orientation, interactivity and learner engagement, contextualized learning feature design, and reflective assessment and feedback. The integration of these principles enables LMS to function as a digital pedagogical environment that supports understanding, reflection, and value transformation. This study contributes a conceptual framework that may serve as an initial reference for future development and research on technology-based Islamic learning.